2020
DOI: 10.1042/cs20200402
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 induces type-2-cytokine phenotype but exacerbates cardiac remodeling post-myocardial infarction with eosinophil recruitment, worsened systolic dysfunction, and ventricular wall rupture

Abstract: Myocardial infarction (MI) is the leading cause of mortality worldwide. Interleukin (IL)-33 (IL-33) is a cytokine present in most cardiac cells and is secreted on necrosis where it acts as a functional ligand for the ST2 receptor. Although IL-33/ST2 axis is protective against various forms of cardiovascular diseases, some studies suggest potential detrimental roles for IL-33 signaling. The aim of the present study was to examine the effect of IL-33 administration on cardiac function post-MI in mice. MI was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 96 publications
2
13
0
Order By: Relevance
“…There are some limitations in this study that deserve acknowledgment. First, apart from its cardioprotective effects, continuous IL‐33 treatment has been observed to increase plasma IL‐5 levels and induce cardiac eosinophilic infiltration both in this and other studies (Abston et al, 2012; Choi et al, 2020; Ghali et al, 2020), which indicates a modification of immune system by IL‐33. However, the effects of these modifications on IL‐33‐derived cardio‐protection are unknown.…”
Section: Discussionsupporting
confidence: 61%
“…There are some limitations in this study that deserve acknowledgment. First, apart from its cardioprotective effects, continuous IL‐33 treatment has been observed to increase plasma IL‐5 levels and induce cardiac eosinophilic infiltration both in this and other studies (Abston et al, 2012; Choi et al, 2020; Ghali et al, 2020), which indicates a modification of immune system by IL‐33. However, the effects of these modifications on IL‐33‐derived cardio‐protection are unknown.…”
Section: Discussionsupporting
confidence: 61%
“…As shown in Table 1, the role of this pathway in cardiac fibrosis is controversial. Sanada et al (2007) observed that the IL-33/ST2 pathway limits overall ventricular fibrosis, whereas Ghali et al (2020) reported IL-33 aggravated the deterioration of cardiac function and cardiac remodeling. In fact, it is associated with activation of myofibroblasts and an increase in the pro-fibrotic markers, such as connective tissue growth factor (CTGF) and TGF-β (Ghali et al, 2020).…”
Section: The Role Of Il-33/st2 Pathway In Renal Fibrosismentioning
confidence: 99%
“…Sanada et al (2007) observed that the IL-33/ST2 pathway limits overall ventricular fibrosis, whereas Ghali et al (2020) reported IL-33 aggravated the deterioration of cardiac function and cardiac remodeling. In fact, it is associated with activation of myofibroblasts and an increase in the pro-fibrotic markers, such as connective tissue growth factor (CTGF) and TGF-β (Ghali et al, 2020). Overall, in majority of fibrotic diseases, this pathway mainly promotes inflammatory responses and facilitates organ fibrosis, ultimately leading to organ dysfunction.…”
Section: The Role Of Il-33/st2 Pathway In Renal Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Among these increased inflammatory gene products are several pro-inflammatory cytokines which play a detrimental role in cardiac physiology (Fig. 5F) (13, 21, 26, 73). Importantly, we also show an increase in plasma levels of TNF-αand IL-6 (Fig.…”
Section: Resultsmentioning
confidence: 99%